Decreased activity with increased background network efficiency in amnestic MCI during a visuospatial working memory task - Lou, Wutao (Hum Brain Mapp, 2015)
Recent studies have demonstrated the working memory impairment in patients with amnestic mild cognitive impairment (aMCI). However, the neurophysiological basis of the working memory deficit in aMCI is poorly understood. The aim of this study was to explore the abnormal activity during encoding and recognition procedures, as well as the reorganization of the background network maintaining the working memory state in aMCI. Using event‐related fMRI during a visuospatial working memory task with three recognition difficulty levels, the task‐related activations and network efficiency of the background network in 17 aMCI patients and 19 matched controls were investigated. Compared with cognitively healthy controls, patients with aMCI showed significantly decreased activity in the frontal and visual cortices during the encoding phase, while during the recognition phase, decreased activity was detected in the frontal, parietal, and visual regions. In addition, increased local efficiency was also observed in the background network of patients with aMCI. The results suggest patients with aMCI showed impaired encoding and recognition functions during the visuospatial working memory task, and may pay more effort to maintain the cognitive state. This study extends our understanding of the impaired working memory function in aMCI and provides a new perspective to investigate the compensatory mechanism in aMCI. Hum Brain Mapp 36:3387–3403, 2015. © 2015 Wiley Periodicals, Inc.